PERENCANAAN PRODUK MINYAK ANGIN AROMA TERAPI KULIT KAYU MANIS MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ayudya Mahendra; Setiawan, Gagok; Handaratri, Anitarakhmi (jurnal ATMOSPHERE, 2022)
The value of Indonesia's biodiversity is very high as can be seen from the many plant species, especially those that can be used as medicine and food, but have not been explored much. One of the plants, namely cinnamon (Cinnamomum burmannii), is already widely known as a raw material for medicine and food. However, a higher value can be extracted from the cinnamon plant by making it a raw material for aromatherapy medicated oil. With the Quality Function Development method, a number of user requirements and technical requirements are prepared that translate the wishes of potential customers for products that match the target market. From the calculation results, the total absolute weight is 1520 and the total relative weight is 900000 so it is predicted that cinnamon aromatherapy medicated oil products can be accepted by the public